Administração estratégica de hospitais: o balanced scorecard e suas contribuições - Teles, João Pedro da Silva (2003)
The dissertation deals with the utilization of The Balanced Scorecard as a mechanism applied to the strategic management process in private hospitais in Brazil. The study evaluates the levei of utilization of this modal in the health care sector and develops a exploratore approach with hospital executivies. Te research leads with the main strategic themes and objectives and the hospital segment in Brazil and analize ir s utilization to develop a generic strategic map addapted to this kind of organization.